Reusable tourniquets for blood sampling as a source of multi-resistant organisms– a systematic review - Szymczyk, Julia; Månsson, Michelle; Mędrzycka-Dąbrowska, Wioletta (Frontiers in Public Health, 2023)
The use of reusable tourniquets is widespread around the world, and reports suggest they may be overused. Several studies have shown that reusable tourniquets can affect the spread of pathogens between patients. The aim of this study is to analyse the indirect transmission of antimicrobial resistant pathogens present on blood collection tourniquets that may spread infectious diseases between patients in daily clinical practice based on available studies. Methods: A systematic review of the literature was conducted according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) protocol guidelines. The contents of PubMed, EBSCO (electronic databases) and Scopus were screened.